Effectiveness of Flood Protection Project Valuation Methods - Liziński, Tadeusz; Bukowski, Marcin; Wróblewska, Anna (Olsztyn Economic Journal, 2015)
Projects for flood protection are increasingly the subject of investment projects in the field of water management. This is related to the increasing frequency of worldwide threats caused by extreme weather conditions, including extremely high rainfall causing floods. Technical and nontechnical flood protection measures are also increasing in importance. In the decision-making process, it is necessary to take into account both the costs and benefits of avoiding losses, including an analysis of social benefits, whose valuation of non-market goods is an essential element. A comprehensive account of projects in the field of flood protection based on the estimated costs and benefits of the investment allows the economic efficiency from a general social point of view to be determined. Previous evaluations of the effectiveness of investment projects have mainly taken into account only categories and market values. The aim of the article is to identify the possibilities to expand the values of non-market assessments and categories formulated on the basis of the theoretical economics of the environment.